Lhermitte–Duclos Disease: Incidental Finding in Traumatic Cerebral Hemorrhage - Beniwal, Hemant Kumar; Satish, Thatikonda; Rao, Gollapudi Prakash; Reddy, Musali Siddartha; Manne, Srikrishnaaditya (Indian Journal of Neurotrauma, 2021)
Lhermitte–Duclos disease, also known as dysplastic cerebellar gangliocytoma, is a rare hamartomatous tumor localized in cerebellum. An association with Cowden syndrome is observed in 50% of cases who present with symptoms of increased intracranial pressure and cerebellar ataxia. These patients have specific magnetic resonance imaging and histopathological findings. Surgical resection is the treatment of choice. Here, we report a case of a young female with traumatic frontal hemorrhage associated with Lhermitte–Duclos disease.
Keywords: Lhermitte–Duclos disease; dysplastic cerebellar gangliocytoma; Cowden disease